Non-thermal plasma activated CO2 hydrogenation over K- and La- promoted layered-double hydroxide supported Ni catalysts - Charalambous, Christina; Xu, Shanshan; Ding, Shengzhe; Chansai, Sarayute; Asuquo, Edidiong; Torres Lopez, Antonio; Parlett, Christopher M. A.; Gilmour, Jamie D.; Garforth, Arthur; Hardacre, Christopher (Frontiers in Chemical Engineering, 2022)
The catalytic conversion of CO2 to CH4 and CO over nickel particles supported on layered-double hydroxide (MgAl) with different metal promoters was investigated under non-thermal plasma (NTP) conditions. It has been shown that lanthanum-promoted Ni catalysts significantly enhanced the CO2 conversion in comparison to the 10Ni/MgAl catalyst (33.4% vs. 89.3%). In comparison, for the potassium-promoted catalysts, CO2 conversion is similar to that of 10Ni/MgAl but the CO selectivity increased significantly (35.7% vs. 62.0%). The introduction of La and K to Ni catalysts increased the Ni dispersion and improved the reducibility of Ni species, thus affecting CO2 conversion and product selectivity. In situ DRIFTS showed similar reaction pathways for La- and K- promoted catalysts with Ni catalysts. However, La and K promoters significantly improved the formation of formate species on the Ni surface, facilitating CO2 conversion to useful products.